SCOF sulfonated polybenzimidazole ion exchange composite membrane and preparation method thereof

By introducing sulfonic acid-functionalized COF into the sulfonated polybenzimidazole membrane, a high-proton-selective nanochannel was constructed, which solved the problem of difficult balance of chemical stability and mechanical properties when the degree of sulfonation was improved, efficient proton conduction and ion selectivity were achieved, and the performance of iron-chromium flow batteries was improved.

CN115763918BActive Publication Date: 2025-04-25BEIJING HERUI ENERGY STORAGE TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211288319.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-20
Publication Date
2025-04-25
Estimated Expiration
2042-10-20

AI Technical Summary

Technical Problem

When the existing sulfonated aromatic polymers improve the degree of sulfonation, it is difficult to balance the chemical stability and mechanical properties, and it is difficult to optimize the equilibrium relationship between proton conductivity and iron-chromium ion permeability.

Method used

By introducing sulfonic acid-functionalized covalent organic framework material (COF) into the sulfonated polybenzimidazole matrix, high proton-selective nanochannels are constructed using the synergistic effect of hydrophilic groups and pore structures to improve the ion selectivity and proton conduction ability of the membrane.

Benefits of technology

High ion selectivity and proton conduction ability are achieved, the iron-chromium flow battery performance and physical and chemical properties of the sulfonated polybenzimidazole composite membrane are improved, and the balance between proton conductivity and iron-chromium ion permeability is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763918B_ABST
    Figure CN115763918B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ion exchange membranes, and specifically discloses a SCOF sulfonated polybenzimidazole ion exchange composite membrane and a preparation method thereof. The SCOF sulfonated polybenzimidazole forming the SCOF sulfonated polybenzimidazole ion exchange composite membrane has a SCOF unit and a sulfonated polybenzimidazole unit. The invention uses the sulfonated polybenzimidazole as a polymer matrix, introduces a sulfonic acid functionalized COF filler into the sulfonated polybenzimidazole matrix, and functionalizes and modifies the sulfonated polybenzimidazole matrix by constructing a high proton selectivity nanochannel through the synergistic effect of a hydrophilic group and a pore structure, so that the composite membrane has high ion selectivity and proton conductivity, and effectively improves the iron-chromium liquid flow battery performance and the physical and chemical properties of the sulfonated polybenzimidazole composite membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ion exchange membranes, and particularly relates to a SCOF sulfonated polybenzimidazole ion exchange composite membrane and a preparation method thereof. Background Art

[0002] Sulfonated aromatic polymers have good thermodynamic stability and conductivity and are expected to become alternative Proton exchange membrane (PEMs) materials for membranes. Generally speaking, increasing the sulfonation degree of sulfonated aromatic polymers can obtain high proton conductivity, but its chemical stability and mechanical properties will decrease. Therefore, it is necessary to modify the sulfonated aromatic polymers to obtain a balance between high proton conductivity and good mechanical properties.

[0003] Sulfonated polybenzimidazole has the advantages of simple preparation, easy availability of raw materials and excellent physical and chemical properties, but the sulfonation degree of the sulfonated polybenzimidazole membrane seriously affects the ion selectivity. For example, the patent with publication number CN105131289A proposes a sulfonated polybenzimidazole copolymer, a cross-linked membrane, and a preparation method. The sulfonated polybenzimidazole copolymer is a sulfonated polybenzimidazole copolymer containing a pendant amino group having the general formula (I):

[0004]

[0005] This patent obtains a polybenzimidazole copolymer containing side amino groups by dissolving aromatic tetraamine, aromatic dicarboxylic acid and aminophthalic acid in polyphosphoric acid and subjecting the mixture to heating, filtering, soaking, washing and drying. The polybenzimidazole copolymer containing side amino groups is then dissolved in concentrated sulfuric acid or fuming sulfuric acid to obtain a sulfonated polybenzimidazole copolymer containing side amino groups. Although this method highly sulfonates the polybenzimidazole, making the flow battery have better energy efficiency and coulombic efficiency, the process is complicated and it is difficult to improve the balance between proton conductivity and iron-chromium ion permeability.

[0006] Therefore, how to optimize the balance between proton conductivity and iron-chromium ion permeability is the key to solving the above problems. Summary of the invention

[0007] In view of the above problems, the present invention discloses a method for preparing a SCOF sulfonated polybenzimidazole ion exchange composite membrane. The SCOF sulfonated polybenzimidazole forming the SCOF sulfonated polybenzimidazole ion exchange composite membrane has a SCOF unit and a sulfonated polybenzimidazole unit:

[0008] The preparation method comprises the following steps:

[0009] Preparation of sulfonated polybenzimidazole and SCOF;

[0010] dissolving the prepared sulfonated polybenzimidazole in dimethyl sulfoxide to obtain a mixed solution;

[0011] Adding SCOF to the mixed solution and performing ultrasonic treatment until a uniform casting solution is obtained;

[0012] The casting solution is cast into a membrane, dried and then immersed in a dilute hydrochloric acid solution, and washed to neutrality to obtain a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane.

[0013] Further, the structural formula of the SCOF unit is as follows:

[0014]

[0015] The structural formula of the sulfonated polybenzimidazole unit is as follows:

[0016]

[0017] Furthermore, the w / v ratio of the sulfonated polybenzimidazole to dimethyl sulfoxide is 3-7%;

[0018] The mass ratio of the sulfonated polybenzimidazole to SCOF is 99:1 to 90:10;

[0019] The concentration of dilute hydrochloric acid is 1-4 mol L -1 .

[0020] Further, the steps of preparing sulfonated polybenzimidazole are as follows:

[0021] dissolving polybenzimidazole in concentrated sulfuric acid to obtain a sulfonated polybenzimidazole solution-sulfuric acid solution;

[0022] The sulfonated polybenzimidazole solution-sulfuric acid solution is poured into ice water to precipitate the sulfonated polybenzimidazole.

[0023] The sulfonated polybenzimidazole precipitate is washed to neutrality, immersed in a sodium bicarbonate solution for 24 hours, and then washed and dried to obtain the sulfonated polybenzimidazole.

[0024] Furthermore, the w / v ratio of the polybenzimidazole to concentrated sulfuric acid is 10-20%;

[0025] The conditions for obtaining the sulfonated polybenzimidazole solution-sulfuric acid solution are: heating to 100-160° C. and maintaining the temperature for 4-12 hours.

[0026] Further, the steps of preparing SCOF are as follows:

[0027] Under nitrogen protection, 1,3,5-triformylphloroglucinol, 2,5-diaminobenzenesulfonic acid, mesitylene and a mixture of 1,4-dioxane and an acetic acid solution are added in sequence to carry out a synthesis reaction;

[0028] After the synthesis reaction is completed, the supernatant is removed by centrifugation to obtain a red precipitate;

[0029] The red precipitate is washed with an organic solvent and dried to obtain SCOF.

[0030] Further, the molar ratio of 1,3,5-triformylphloroglucinol to 2,5-diaminobenzenesulfonic acid is 2:3;

[0031] The mesitylene, 1,4-dioxane and 3 mol L -1 The volume ratio of acetic acid is 1:4:0.5;

[0032] The w / v ratio of the 1,3,5-triformylphloroglucinol to mesitylene is 2-5%.

[0033] Further, the conditions of the mixed reaction are: 120°C for 72h;

[0034] The organic solvent is a mixture of anhydrous DMF, anhydrous dichloromethane and anhydrous acetone in a volume ratio of 1:1:1.

[0035] On the other hand, the present invention also provides a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane prepared by the above preparation method.

[0036] Furthermore, the SCOF sulfonated polybenzimidazole forming the SCOF sulfonated polybenzimidazole ion exchange composite membrane has a SCOF unit and a sulfonated polybenzimidazole unit:

[0037] The structural formula of the SCOF unit is as follows:

[0038]

[0039] The structural formula of the sulfonated polybenzimidazole unit is as follows:

[0040]

[0041] Beneficial effects of the present invention:

[0042] The present invention uses sulfonated polybenzimidazole as a polymer matrix, introduces sulfonic acid functionalized COF (covalent organic framework) filler into the sulfonated polybenzimidazole matrix, and functionalizes it by constructing a high proton-selective nanochannel through the synergistic effect of hydrophilic groups and pore structures, so that the composite membrane has high ion selectivity and proton conductivity, effectively improving the iron-chromium liquid flow battery performance and physical and chemical properties of the sulfonated polybenzimidazole composite membrane.

[0043] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0045] Figure 1 A flow chart of preparing a SCOF sulfonated polybenzimidazole ion exchange composite membrane in an embodiment of the present invention is shown;

[0046] Figure 2 The structure diagram of the iron-chromium liquid flow single cell test system assembled in the test example of the present invention is shown; in the figure: 1, iron-chromium liquid flow single cell; 2, positive electrode storage tank and electrolyte; 3, negative electrode storage tank and electrolyte; 4, positive electrode pipeline; 5, negative electrode pipeline; 6, current collecting plate;

[0047] Figure 3 The coulombic efficiency test results of the SCOF sulfonated polybenzimidazole ion exchange composite membranes prepared in Examples 1-3 of the present invention are shown;

[0048] Figure 4 The voltage efficiency test results of the SCOF sulfonated polybenzimidazole ion exchange composite membranes prepared in Examples 1-3 of the present invention are shown;

[0049] Figure 5 The energy efficiency test results of the SCOF sulfonated polybenzimidazole ion exchange composite membranes prepared in Examples 1-3 of the present invention are shown. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] In view of the problem that the chemical stability and mechanical properties of sulfonated aromatic polymers are reduced in the process of increasing the sulfonation degree of sulfonated aromatic polymers in the prior art, and co-modification is a commonly used modification method, which can be used as a filler to improve the performance of polymer electrolyte membranes. How to apply covalent organic framework covalent organic framework materials (COFs) and sulfonated polybenzimidazole is a development direction. Based on this, the present invention provides a SCOF sulfonated polybenzimidazole ion exchange composite membrane preparation method, by introducing sulfonic acid functionalized COF into a sulfonated polybenzimidazole matrix, wherein the covalent organic framework material has a high specific surface area, adjustable pore size, long-range ordered porous structure, good chemical stability and thermal stability. Through the synergistic effect of hydrophilic groups and pore structures to construct high proton selective nanochannels, high ion conductivity and high selectivity are ensured, and excellent iron-chromium liquid flow battery performance is achieved. In order to solve the problem that the existing proton exchange membrane is difficult to achieve a balanced relationship between proton conductivity and iron-chromium ion permeability in applications.

[0052] The SCOF (COF with sulfonic acid group) enhanced sulfonated polybenzimidazole ion exchange composite membrane comprises SCOF unit and sulfonated polybenzimidazole unit.

[0053] The structural formula of the sulfonated polybenzimidazole unit is as follows:

[0054]

[0055] The structural formula of the SCOF unit is as follows:

[0056]

[0057] Before using SCOF to enhance the sulfonated polybenzimidazole ion exchange composite membrane, COF and polybenzimidazole need to be sulfonated. The specific process is as follows: Figure 1 As shown:

[0058] The preparation of sulfonated polybenzimidazole comprises the following steps:

[0059] Dissolving polybenzimidazole in concentrated sulfuric acid, heating to 100-160° C. and maintaining the temperature for 4-12 hours to obtain a sulfonated polybenzimidazole solution-sulfuric acid solution;

[0060] The sulfonated polybenzimidazole solution-sulfuric acid solution is poured into ice water to precipitate the sulfonated polybenzimidazole; the ice water can quickly terminate the sulfonation reaction, so that the sulfonation degree of the sulfonated polybenzimidazole can be controlled, and the ice water can effectively absorb the heat released by the concentrated sulfuric acid entering the water.

[0061] After washing the precipitate to neutrality, soak it in a sodium bicarbonate solution for 24 hours, and finally wash it with deionized water until the pH is neutral, and dry it to obtain the sulfonated polybenzimidazole material. After the reaction is completed, slowly pour the mixture into ice water under stirring. Sodium bicarbonate can convert H-type sulfonated polybenzimidazole into Na-type sulfonated polybenzimidazole, which increases the solubility of sulfonated polybenzimidazole and facilitates subsequent film casting.

[0062] Wherein, the w / v (mass / volume, unit is g / mL) of polybenzimidazole and concentrated sulfuric acid is 10-20%;

[0063] The mass fraction of sodium bicarbonate solution is 3-7%;

[0064] The sulfonation degree of the sulfonated polybenzimidazole is 100 to 130%.

[0065] Drying conditions: Dry at 40-80°C to constant weight.

[0066] The preparation of SCOF comprises the following steps:

[0067] Under nitrogen protection, 1,3,5-triformylphloroglucinol, 2,5-diaminobenzenesulfonic acid, mesitylene, 1,4-dioxane and 3 mol L -1 Acetic acid solution. React at 120℃ for 72h. After the reaction, centrifuge and remove the supernatant to obtain a red precipitate, which is washed with anhydrous DMF, anhydrous dichloromethane and anhydrous acetone and dried to obtain a sulfonated organic covalent framework (SCOF) product. Among them, the formyl group and amino group in 1,3,5-triformylphloroglucinol and 2,5-diaminobenzenesulfonic acid form a covalent bond to form an orderly infinitely extended structure, namely SCOF.

[0068] Wherein, the molar ratio of 1,3,5-triformylphloroglucinol to 2,5-diaminobenzenesulfonic acid is 2:3;

[0069] Mesitylene, 1,4-dioxane and 3 mol L -1 The volume ratio of acetic acid is 1:4:0.5;

[0070] The w / v (mass / volume, unit is g / mL) of 1,3,5-triformylphloroglucinol and mesitylene is 2-5%;

[0071] Drying conditions: Dry at 60-100°C to constant weight.

[0072] In this application, the SCOF enhanced sulfonated polybenzimidazole ion exchange composite membrane is prepared according to the following steps:

[0073] Dissolve sulfonated polybenzimidazole in dimethyl sulfoxide, stir and mix well, and then add SCOF to the mixture. After ultrasonic treatment, a uniform casting solution is obtained; the casting solution is cast into a membrane, and dried to obtain a film; the membrane is immersed in 1-4 mol L -1 The membrane was placed in a dilute hydrochloric acid solution for 12 to 48 hours, and then soaked and washed with deionized water until neutral, thereby obtaining a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane.

[0074] The dilute hydrochloric acid solution is mainly used to convert the Na-type sulfonated polybenzimidazole in the SCOF enhanced sulfonated polybenzimidazole ion exchange composite membrane into the H-type sulfonated polybenzimidazole, thereby improving the proton conductivity of the membrane and increasing the stability of the electrochemical test.

[0075] The w / v ratio of the sulfonated polybenzimidazole to dimethyl sulfoxide is 3-7%;

[0076] The mass ratio of the sulfonated polybenzimidazole to SCOF is 99:1 to 90:10;

[0077] Drying conditions: temperature is 60-100°C, and time is drying to constant weight.

[0078] Example 1

[0079] (1) Add 5 g of polybenzimidazole and 75 mL of concentrated sulfuric acid into a flask to form a mixture, slowly heat the mixture to 130°C and maintain it at this temperature for 8 hours. After the reaction is completed, slowly pour the solution mixture into ice water while stirring. Collect the precipitate by filtration, wash it to neutrality, soak it in a 5% sodium bicarbonate solution for 24 hours, and finally wash it with deionized water until the pH is neutral. Dry to obtain a sulfonated polybenzimidazole material with a sulfonation degree of 121%;

[0080] (2) Under nitrogen protection, 1,3,5-triformylphloroglucinol, 2,5-diaminobenzenesulfonic acid, a mixture of mesitylene and 1,4-dioxane and 3 mol L -1 The volume ratio of acetic acid solution, mesitylene, 1,4-dioxane and 3 mol L-1 acetic acid is 1:4:0.5. The reaction is carried out at 120°C for 72 hours. After the reaction is completed, the supernatant is centrifuged to obtain a red precipitate, which is washed with anhydrous DMF, anhydrous dichloromethane and anhydrous acetone and dried to obtain a sulfonated organic covalent framework (SCOF) product.

[0081] (3) Dissolve sulfonated polybenzimidazole in dimethyl sulfoxide, the w / v ratio of sulfonated polybenzimidazole to dimethyl sulfoxide is 3%, unit is g / mL, stir and mix evenly, add SCOF to the mixture, the mass ratio of sulfonated polybenzimidazole to SCOF is 99:1. After ultrasonic treatment, a uniform casting solution is obtained; cast the casting solution into a film, dry it, and obtain a film; soak the film in 2 mol L -1 After being immersed in a dilute hydrochloric acid solution for 12 hours, the membrane was soaked and washed with deionized water until neutral, thereby obtaining a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane named SPBI-SCOF-1%.

[0082] Example 2

[0083] (1) Add 5g polybenzimidazole and 75mL concentrated sulfuric acid into a flask to form a mixture, slowly heat the mixture to 130°C and keep it at this temperature for 8 hours. After the reaction is completed, slowly pour the solution mixture into ice water under stirring. Collect the precipitate by filtration, wash it to neutrality, soak it in a 6% sodium bicarbonate solution for 24 hours, and finally wash it with deionized water until the pH is neutral. Dry to obtain a sulfonated polybenzimidazole material with a sulfonation degree of 120%;

[0084] (2) Under nitrogen protection, 1,3,5-triformylphloroglucinol, 2,5-diaminobenzenesulfonic acid, a mixture of mesitylene and 1,4-dioxane and 3 mol L -1 The volume ratio of acetic acid solution, mesitylene, 1,4-dioxane and 3 mol L-1 acetic acid is 1:4:0.5. The reaction is carried out at 120°C for 72 hours. After the reaction is completed, the supernatant is centrifuged to obtain a red precipitate, which is washed with anhydrous DMF, anhydrous dichloromethane and anhydrous acetone and dried to obtain a sulfonated organic covalent framework (SCOF) product.

[0085] (3) Dissolve sulfonated polybenzimidazole in dimethyl sulfoxide, the w / v ratio of sulfonated polybenzimidazole to dimethyl sulfoxide is 3%, unit is g / mL, stir and mix evenly, add SCOF to the mixture, the mass ratio of sulfonated polybenzimidazole to SCOF is 97:3. After ultrasonic treatment for a period of time, a uniform casting solution is obtained; cast the casting solution into a membrane, dry it, and obtain a membrane; soak the membrane in 1 mol L -1 After being immersed in a dilute hydrochloric acid solution for 48 hours, the membrane was soaked and washed with deionized water until neutral, thereby obtaining a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane named SPBI-SCOF-3%.

[0086] Example 3

[0087] (1) Add 5 g of polybenzimidazole and 75 mL of concentrated sulfuric acid into a flask to form a mixture, slowly heat the mixture to 130°C and maintain it at this temperature for 8 hours. After the reaction is completed, slowly pour the solution mixture into ice water while stirring. Collect the precipitate by filtration, wash it to neutrality, soak it in a 7% sodium bicarbonate solution for 24 hours, and finally wash it with deionized water until the pH is neutral. Dry to obtain a sulfonated polybenzimidazole material with a sulfonation degree of 117%;

[0088] (2) Under nitrogen protection, 1,3,5-triformylphloroglucinol, 2,5-diaminobenzenesulfonic acid, a mixture of mesitylene and 1,4-dioxane and 3 mol L -1 The volume ratio of acetic acid solution, mesitylene, 1,4-dioxane and 3 mol L-1 acetic acid is 1:4:0.5. The reaction is carried out at 120°C for 72 hours. After the reaction is completed, the supernatant is centrifuged to obtain a red precipitate, which is washed with anhydrous DMF, anhydrous dichloromethane and anhydrous acetone and dried to obtain a sulfonated organic covalent framework (SCOF) product.

[0089] (3) Dissolve sulfonated polybenzimidazole in dimethyl sulfoxide, the w / v ratio of sulfonated polybenzimidazole to dimethyl sulfoxide is 3%, unit is g / mL, stir and mix evenly, then add SCOF to the mixture, the mass ratio of sulfonated polybenzimidazole to SCOF is 95:5. After ultrasonic treatment for a period of time, a uniform casting solution is obtained; cast the casting solution into a membrane, dry it, and obtain a membrane; soak the membrane in 4 mol L -1 After being immersed in a dilute hydrochloric acid solution for 12 hours, the membrane was soaked and washed with deionized water until neutral, thereby obtaining a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane named SPBI-SCOF-5%.

[0090] Example 4

[0091] The amount of concentrated sulfuric acid in step (1) of Example 1 was changed to 50 mL, and the other conditions remained unchanged. The sulfonation degree of the obtained sulfonated polybenzimidazole was 120%, and a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane was obtained.

[0092] Example 5

[0093] The amount of concentrated sulfuric acid in step (1) of Example 1 was changed to 100 mL, and the other conditions remained unchanged. The degree of sulfonation of the obtained sulfonated polybenzimidazole was 119%, and a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane was obtained.

[0094] Example 6

[0095] The sodium bicarbonate in step (1) of Example 1 was replaced with a mass fraction of 3%, and the other conditions remained unchanged. The obtained sulfonated polybenzimidazole had a sulfonation degree of 120%, and a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane was obtained.

[0096] Example 7

[0097] The w / v ratio of sulfonated polybenzimidazole to dimethyl sulfoxide in step (3) of Example 1 was changed to 7%, and other conditions remained unchanged to prepare a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane.

[0098] Example 8

[0099] The mass ratio of sulfonated polybenzimidazole to SCOF in step (3) of Example 1 was set to 90:10, and the other conditions remained unchanged to obtain a SCOF-reinforced sulfonated polybenzimidazole ion exchange composite membrane.

[0100] Comparative Example 1

[0101] The other conditions remained unchanged, polybenzimidazole was sulfonated according to the method of step (1) of Example 1, and then membrane was prepared according to the method of step (3) without adding SCOF, to obtain a sulfonated polybenzimidazole ion exchange composite membrane, named SPBI.

[0102] Comparative Example 2

[0103] The step of sulfonating polybenzimidazole according to step (1) of Example 1 is changed to: the mixture is slowly heated to 110° C. and maintained at this temperature for 5 hours, while the other conditions remain unchanged; and the membrane is then prepared according to the method of step (3) without adding SCOF, and the sulfonation degree of the sulfonated polybenzimidazole ion exchange membrane is 100%.

[0104] Comparative Example 3

[0105] The step of sulfonating polybenzimidazole according to step (1) of Example 1 is changed to: the mixture is slowly heated to 140° C. and maintained at this temperature for 12 hours, while the other conditions remain unchanged; and the membrane is then prepared according to the method of step (3) without adding SCOF, and the sulfonation degree of the sulfonated polybenzimidazole ion exchange membrane is 130%.

[0106] Test Example 1

[0107] Two graphite felt electrodes were used as the positive electrode and the negative electrode respectively, and the composite membranes prepared in Examples 1-8 and Comparative Examples 1-3 were used as the diaphragm to form a single cell. The iron-chromium liquid flow battery electrolyte was added to form an iron-chromium liquid flow single cell test system to test the battery's charge and discharge performance. The assembled iron-chromium liquid flow single cell test system is shown in the figure below: Figure 2As shown, one end of the positive electrode pipeline 4 and one end of the negative electrode pipeline 5 connect the iron-chromium liquid flow single cell 1 to the charging and discharging machine through the current collecting plate 6, wherein the other end of the positive electrode pipeline 4 is arranged in the positive electrode storage tank and the electrolyte, and the other end of the negative electrode pipeline 5 is connected to the negative electrode storage tank and the electrolyte 2.

[0108] The Fe-Cr flow cell test system was tested at 30, 50, 70, 90 and 110 mA cm -2 The battery performance test was carried out under constant current charge and discharge conditions to test its coulombic efficiency (CE, %), voltage efficiency (VE, %) and energy efficiency (EE, %). The results are shown in Tables 1 to 5 respectively:

[0109] Table 1 30mA·cm -2 Testing cell performance of iron-chromium flow battery

[0110]

[0111]

[0112] Table 2 50mA·cm -2 Testing cell performance of iron-chromium flow battery

[0113]

[0114] Table 3 70mA·cm -2 Testing cell performance of iron-chromium flow battery

[0115]

[0116]

[0117] Table 4 90mA·cm -2 Testing cell performance of the iron-chromium flow battery

[0118]

[0119] Table 5 110mA·cm -2 Testing cell performance of the iron-chromium flow battery

[0120]

[0121]

[0122] The coulombic efficiency (CE, %), voltage efficiency (VE, %) and energy efficiency (EE, %) of the SCOF sulfonated polybenzimidazole ion exchange composite membranes prepared in Examples 1-3 were compared and analyzed. The test results of the coulombic efficiency are shown in FIG. Figure 3 As shown in the figure, the test results of voltage efficiency are as follows Figure 4 The energy efficiency test results are shown in Figure 5 As shown, it can be seen that with the increase of SCOF doping amount, the CE of the membrane gradually increases, and the VE decreases slightly, but it is still higher than SPBI (control group, i.e., sulfonated polybenzimidazole without SCOF addition, comparative example 1). This is because the introduction of SCOF can better screen protons, thereby improving selectivity. At the same time, due to the presence of sulfonic acid groups on SCOF, the conductivity is also improved. However, with the increase of SCOF doping amount, the agglomeration of SCOF in the membrane is inevitably aggravated, which is not conducive to the conduction of protons, causing the conductivity of the membrane to decrease slightly. In general, the best CE is SPBI-SCOF-5%, but the best EE is SPBI-SCOF-1%. At 70mAcm -2 At a current density of 1.34 W, the CE, VE and EE of the SPBI-SCOF-1% membrane were 96.63%, 85.87% and 82.98%, respectively.

[0123] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a SCOF sulfonated polybenzimidazole ion exchange composite membrane, characterized in that: The SCOF sulfonated polybenzimidazole forming the SCOF sulfonated polybenzimidazole ion exchange composite membrane has a SCOF unit and a sulfonated polybenzimidazole unit: The structural formula of the SCOF unit is as follows: The structural formula of the sulfonated polybenzimidazole unit is as follows: ; The preparation method comprises the following steps: Preparation of sulfonated polybenzimidazole and SCOF; dissolving the prepared sulfonated polybenzimidazole in dimethyl sulfoxide to obtain a mixed solution; Adding SCOF to the mixed solution and performing ultrasonic treatment until a uniform casting solution is obtained; The casting solution is cast into a membrane, dried and then immersed in a dilute hydrochloric acid solution, and washed to neutrality to obtain a SCOF-enhanced sulfonated polybenzimidazole ion exchange composite membrane.

2. The method for preparing the SCOF sulfonated polybenzimidazole ion exchange composite membrane according to claim 1, characterized in that: The w / v ratio of the sulfonated polybenzimidazole to dimethyl sulfoxide is 0.03 to 0.07, in g / mL; The mass ratio of the sulfonated polybenzimidazole to SCOF is 99:1 to 90:10; The concentration of dilute hydrochloric acid is 1-4 mol L -1 .

3. The method for preparing the SCOF sulfonated polybenzimidazole ion exchange composite membrane according to claim 1, characterized in that: The steps for preparing sulfonated polybenzimidazole are as follows: dissolving polybenzimidazole in concentrated sulfuric acid to obtain a sulfonated polybenzimidazole solution-sulfuric acid solution; The sulfonated polybenzimidazole solution-sulfuric acid solution is poured into ice water to precipitate the sulfonated polybenzimidazole. The sulfonated polybenzimidazole precipitate is washed to neutrality, immersed in a sodium bicarbonate solution for 24 hours, and then washed and dried to obtain the sulfonated polybenzimidazole.

4. The method for preparing the SCOF sulfonated polybenzimidazole ion exchange composite membrane according to claim 3, characterized in that: The w / v ratio of the polybenzimidazole to concentrated sulfuric acid is 0.05 to 0.1, in g / mL; The conditions for obtaining the sulfonated polybenzimidazole solution-sulfuric acid solution are: heating to 100-160° C. and maintaining the temperature for 4-12 hours.

5. The method for preparing the SCOF sulfonated polybenzimidazole ion exchange composite membrane according to claim 1, characterized in that: The steps for preparing SCOF are as follows: Under nitrogen protection, 1,3,5-triformylphloroglucinol, 2,5-diaminobenzenesulfonic acid, mesitylene and a mixture of 1,4-dioxane and an acetic acid solution are added in sequence to carry out a synthesis reaction; After the synthesis reaction is completed, the supernatant is removed by centrifugation to obtain a red precipitate; The red precipitate is washed with an organic solvent and dried to obtain SCOF.

6. The method for preparing the SCOF sulfonated polybenzimidazole ion exchange composite membrane according to claim 5, characterized in that: The molar ratio of 1,3,5-triformylphloroglucinol to 2,5-diaminobenzenesulfonic acid is 2:3; The mesitylene, 1,4-dioxane and 3 mol L -1 The volume ratio of acetic acid is 1:4:0.5; The w / v ratio of the 1,3,5-triformylphloroglucinol to mesitylene is 0.02-0.05, and the unit is g / mL.

7. The method for preparing the SCOF sulfonated polybenzimidazole ion exchange composite membrane according to claim 5, characterized in that: The conditions of the mixed reaction were: 120 °C for 72 h; The organic solvent is a mixture of anhydrous DMF, anhydrous dichloromethane and anhydrous acetone in a volume ratio of 1:1:

1.

8. A SCOF sulfonated polybenzimidazole ion exchange composite membrane, characterized in that: The SCOF sulfonated polybenzimidazole ion exchange composite membrane is prepared by the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Novel sulfonated polybenzimidazole copolymer, crosslinked membrane, preparation method and application thereof

    CN105131289A

  • Sulfonated polybenzimidazole proton exchange membrane, preparation method and application

    CN108649256A

  • Heteroatom-containing covalent organic framework electrode material and preparation method and application thereof

    CN111682207A